Glacier outlines of Hallstätter Glacier, Austria, 1856 et seq in shapefile format - Kay Helfricht; Giulia Bertolotti; Lea Hartl; Martin Stocker-Waldhuber; Klaus Reingruber; Diana-Eileen Kara; Andrea Fischer (PANGAEA, 2024)
Glacier outlines of Hallstätter Glacier in the Dachstein Massif, Austria, are periodically mapped as part of the respective glacier mass balance monitoring program. Outlines are provided in shapefile format and were mapped based on the available DEMs, historical images, orthophotos or satellite images. Glacier area has decreased from 5.3 km2 in 1856 to 2.4 km2 in 2023. Detailed Information is given in Helfricht (2009), Kara (2020) and Bertolotti et al. (in prep.) and in the associated readme files. New outlines will be added as they become available.